TEACHING MATHEMATICS MOTIVATED BY PHYSICS - FAJMON, Břetislav (Trends in education, 2018)
The article gives examples of interconnectedness between mathematics and physics: completing physic with the appropriate mathematical apparatus, or on the other hand, putting in physical applications with mathematical notions. The second part deals with the possibility of creating a syllabus of mathematics and physics taught as one subject, especially at grammar schools.
Keywords: teaching mathematics; teaching physics; motivation in physics; subject interconnected-ness